η8-Permethylpentalene Titanium Chemistry - Cooper, RT (2012)
The focus of this thesis is the synthesis of organometallic complexes incorporating the η8-permethylpentalene titanium moiety (η8-Pn*Ti), their characterisation, and their reactivity with small molecules. Chapter One summarises the chemistry of the pentalene molecule, from its instability in the free state to the incorporation of the hydrocarbon into organometallic complexes. The chapter continues with a review of the coordination modes available to Pn and concludes with a brief discussion on the effects of permethylation of hydrocarbon ligands and the advent of permethylpentalene (Pn*). Chapter Two documents the improved synthesis of [Pn*TiCl(μ-Cl)]2 utilising isomeric control imparted on the Pn* synthon, Pn*(SnMe3)2. This protocol permits access to a variety of methylated compounds through metathesis chemistry, of which five have been crystallographically elucidated, revealing the fold angle to be reliant on an interplay between steric and electronic factors. Mono-, bi- and trimetallic {Pn*TiMe2, [Pn*TiMe(μ-Cl)]2 and [Pn*Ti(μ-Me)]2(μ-CH2), and [Pn*TiMe(μ-Me)2]2Mg respectively} species were synthesised dependent on the methylating agent employed and they displayed varying thermal stabilities, with the dimeric nature of [Pn*TiMe(μ-Cl)]2 proving crucial in the formation of [Pn*Ti(μ-Cl)]2(μ-CH2). Chapter Three describes the incorporation of classical organometallic ligands into the Pn*Ti moiety, including the first examples of benzyl, alkyl, aryl, allyl and η1-Cp bound to a PnTi fragment. Seven complexes have been structurally characterised including the first ever crystal structure of a π-hydrocarbon bound Ti species bearing two CH2tBu groups, Pn*Ti(CH2tBu)2, and the fluxional mixed hapticity complex Pn*Ti(η5-Cp)(η1-Cp), whose η1-Cp rearranges via a 1,2-sigmatropic shift. Chapter Four investigates the reactivity of the monomeric dialkyls, Pn*TiR2 (R = Me, CH2Ph, CH2SiMe3 and CH2tBu) with CO2, CO and H2. All four compounds demonstrate “normal” insertion of the CO2 moiety into both Ti-R bonds, revealing a symmetrical bidentate coordination of the RCO2 units. Computational studies have highlighted two competing pathways for their reaction with CO, dependent on the concentration of CO and size of R, which results either in formation of an enediolate or a titanoxirane. The reaction with H2 yields the fascinating trimeric mixed valence, [Pn*Ti(μ2-H)]3(μ3-H), the first structurally characterised example of a trimeric Ti-H species and the first to include a Ti-(μ3-H) moiety. (Pn*TiCl)2(μ-O) is formed by the action of adventitious H2O and possesses a linear Ti-O-Ti bridge with a degree of Ti-O double bond character, supported by crystallographic data and DFT calculations. Chapter Five discusses ethylene polymerisation studies on the monomeric dialkyl complexes Pn*TiR2 (R = Me, CH2Ph, CH2SiMe3 and CH2tBu) using the activators [Ph3C][B(C6F5)4], [PhNMe2H][B(C6F5)4], AliBu3 and H2. Chapter Six presents full experimental procedures for all of the syntheses and reactions outlined in Chapters Two to Five. Chapter Seven details characterising data for all novel compounds, and crystallographic data in the form of CIF files may be found in the electronic